Microshear bond strength of composite resin to demineralized dentin after remineralization with sodium fluoride, CPP-ACP and NovaMin containing dentifrices - Banka Krithi; Sampath Vidhya; Sekar Mahalaxmi (Journal of Oral Biology and Craniofacial Research)
Background: Bonding composite to remineralized dentin is challenging. The aim of this study was to evaluate the microshear bond strength (μSBS) of composite to demineralized dentin, which had been remineralized with sodium fluoride (NaF), CPP-ACP and NovaMin containing dentifrices. Materials and methods: 108 extracted human premolars or molars were sectioned longitudinally into buccal and lingual halves (n = 216). Dentin (3 × 3 mm) was exposed on the cervical aspect of teeth and the samples were allotted randomly to six groups (n = 36) according to the remineralizing agent used namely, group 1 (sound dentin), group 2 (demineralized dentin), group 3 (NaF), group 4 (CPP-ACP), group 5 (NovaMin) and group 6 (non-fluoridated). The type of bonding system (total-etch or self-etch) formed the subgroups. Samples in groups 2–6 were submitted to an acid challenge for 3 days followed by remineralization in groups 3–6 for 90 days. Etching pattern (n = 3) was observed under SEM. μSBS of the bonded samples (n = 15) were evaluated. The data were statistically analyzed using Kruskal Wallis and Dunn's Post Hoc tests (p < 0.05). Results: SEM micrographs of remineralized samples showed varying degrees of partially occluded and exposed dentinal tubules. Under both the adhesives, the mean μSBS of composite in groups 2–6 was lesser than that of group 1. Among self-etch subgroups, μSBS of NaF group was not significantly different from that of normal dentin. Conclusion: Composite forms a weaker bond to remineralized dentin. Self-etch bonding system is capable of achieving acceptable bond strength to dentin remineralized with NaF and NovaMin.